Pendidikan Agama Islam sebagai Fondasi Pembentukan Karakter Siswa Sekolah Dasar: Analisis Konseptual Berbasis Studi Kepustakaan - Mohamad Junedin; Mukarom Mukarom (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study analyzes the role of Islamic Religious Education (IRE) as a foundation for character formation in elementary school students using a qualitative library research approach. The study examines major works in character education and Islamic pedagogy to synthesize theoretical perspectives on the integration of religious values in basic education. The findings show that IRE contributes to the development of religious awareness, honesty, discipline, responsibility, and social care when implemented holistically through teacher role modeling, habituation of worship practices, integration of Islamic values into school culture, and collaboration between school and family. This study proposes a conceptual synthesis that positions IRE not only as a subject of instruction but as a foundational moral framework for character education. By integrating modern character education theory with Islamic educational philosophy, this research provides a theoretical explanation of how IRE functions as a structural basis for sustainable character formation in elementary education.